Limited Benefit of Fatmax-Test to Derive Training Prescriptions - Schwindling, S.; Scharhag-Rosenberger, F.; Kindermann, W.; Meyer, T. (International Journal of Sports Medicine, 2014)
The intensity that elicits maximal fat oxidation (Fatmax) is recommended for training fat metabolism. However, it remains unclear whether Fatmax leads to the highest fat oxidation rates during prolonged exercise. It was hypothesized that there are no differences in fat oxidation rates among 3 different exercise intensities. Therefore, fat metabolism was compared among 1-h constant load tests at Fatmax, a higher and a lower intensity. A cohort of 16 male cyclists (28±6 yrs, BMI: 22.5±1.2 kg/m2; n=8 with maximal oxygen uptake [VO2max] of 50–60 ml/min/kg [ET]; n=8 with VO2max>60 ml/min/kg [HET]) completed a maximal incremental cycling test, a submaximal incremental Fatmax-test and, thereafter, three 1-h constant-load tests in randomized order at Fatmax, one exercise stage below (LOW) and one above (HIGH). LOW, Fatmax and HIGH were performed at 52±13, 60±13 and 70±12% VO2max. Heart rate and blood lactate were significantly different (p<0.001). However, the fat oxidation rate showed no difference (p=0.61). This was also true within each subgroup (ET: p=0.69, HET p=0.61). In conclusion, the fat oxidation rate of endurance trained cyclists shows no difference between 1-h constant load exercise bouts at about 50–70% VO2max. The precision and necessity of Fatmax-tests for controlling the training of fat oxidation are therefore debatable.
Keywords: fat metabolism; fat oxidation; indirect calorimetry; intensity; cycling; training